2021
DOI: 10.20511/pyr2021.v9nspe3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Management Model of Energy Enterprises Innovative Development Within Physiological Working Conditions

Abstract: Accordingly, innovative solutions aimed at improving sales should receive a response to gross sales revenue. The management mathematical dynamic models proposed in the work scientifically substantiate the decisions made and allow predicting the influence of the system of innovative development factors and physiological working conditions of employees on the financial condition of the enterprise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…«Головною особливістю процесів проєктно-орієнтованої організації є їх стандартна структура і стандартні обмеження, саме ці стандартні обмеження за часом, вартістю реалізації проєктів і за якістю результатів можна використати для побудови узагальненого показника, що характеризує ділові процеси проєкту через оцінку відхилень, що виникають» [8].…”
Section: п микитюк ю микитюкunclassified
“…«Головною особливістю процесів проєктно-орієнтованої організації є їх стандартна структура і стандартні обмеження, саме ці стандартні обмеження за часом, вартістю реалізації проєктів і за якістю результатів можна використати для побудови узагальненого показника, що характеризує ділові процеси проєкту через оцінку відхилень, що виникають» [8].…”
Section: п микитюк ю микитюкunclassified
“…According to Xie et al (2020), it requires up-to-date information on traffic flow from different sources in different areas, such as mobile phone data, taxi trajectory data, metro/bus travel data, bicycle exchange data. At the same time, following the principles of urban ecology, the level of transport diversification is increasing through using environmentally friendly modes of transport as a contribution to improving the sustainable development of urban mobility (Deschenes et al, 2020;Nguyen-Phuoc et al, 2020;Lokhandwala and Hua, 2020;Liakhovych et al, 2021;Welch et al, 2020;Brych et al, 2021). Welch et al (2020) showed that the travel cost and natural factors, land diversity, and connectivity indicators affect the choice of transport mode (taxi or bicycle, rather than rail).…”
Section: Introductionmentioning
confidence: 99%
“…-зона прискореної реалізації проєкту; 2 -світовий рівень; 3 -зона нормативної тривалості; 4 -зона існуючого стану.Можна виокремити дві зони виконання робіт: зона оптимізації інтенсивності та зона вимушеної інтенсивності[9]. Перша характеризується тим, що зменшення часу виконання робіт за рахунок підвищення інтенсивності призводить до зростання витрат організації, з іншого боку, для зменшення відповідних витрат необхідне зниження інтенсивності виконання робіт.…”
unclassified